Movimientos (Trans) Feministas del Ecuador :El caso de la Marcha de la putas - Quito - Hernández Mosquera, Yolanda Guadalupe (2015)
This document is the result of fieldwork conducted between 2014 and 2015 in the movement and action Slut Walk - Ecuador. This initiative was born in Canada in 2011, to reject sexist comments that blame women for rape upon them by the way they dress; and it has expanded around the world. In Ecuador’s case, its development is particularly interesting because it provides a political content that feeds feminism and transfeminism that is widely emerging through this, it is under construction and this is what caught my attention. For this, a research participant observation that allowed walk three categories of analysis (shafts sense, isotopies): Temporality, spatiality and meaning. Discourses and practices that support and supported by the patriarchal system in Ecuador has generated social mobilization to confront, however it is in a moment of transformation. This situation is not alien to feminism and activism but transfeminism presents the theoretical, practical an political contributions that are embodied in this movement and action Slutwalk - Ecuador.